Opportunities for the Philippines under RCEP: Trade in services - John Paolo R. Rivera; Tereso S. Tullao (Philippine Institute for Development Studies (PIDS), 2022)
The Regional Comprehensive Economic Partnership (RCEP) is a forward-looking trade agreement between member economies of the Association of Southeast Asian Nations (ASEAN) and its free trade agreement (FTA) partners (AFPs) namely Australia, China, Japan, Korea, and New Zealand (i.e., non-ASEAN signatory economies). It presents an opportunity to participating economies to consolidate rules given overlapping sets of FTAs. Because of stalemates that developed between economies in World Trade Organizat ion (WTO) negotiations, more regional trading agreements (RTAs) have emerged. As RTAs define trade rules and commitments for all its signatories that are geared towards encouraging free movement of goods and services among member economies, it can deepen economic linkages. The RCEP is an alternative avenue for trade liberalization at the regional level, and a challenger to the Trans-Pacific Partnership (TPP) in terms of coverage and degree of liberalization. Through RCEP, new opportunities for trade and investment may be harnessed. As a result, the enhanced partnership can contribute to human resource and infrastructure development - which are key to the economic growth and development of the Philippines. Hence, we investigate how the RCEP can deepen the contributions of trade in services in the Philippine economy through the commitments made and limitations imposed. We reviewed and assessed the specific commitments of AFPs joining the RCEP in terms of trade in services, particularly on market access and national treatment. We compared these commitments, evaluated its relevance to the needs of the Philippines, and determined the benefits that he Philippines can reap from RCEP. Our analysis suggests that the RCEP is a marginal regional trading arrangement that should be viewed as a compilation of previous regional trading agreements for key economies in the Asia-Pacific (APAC) region. Because of the additional commitments made by the signatory economies, specific opportunities in trade in services may be valuable for the Philippines. However, there are challenges in the form of market access and national treatment limitations, which the Philippines must view as an opportunity to enhance its domestic productivity.
Keywords: 330; ASEAN; free trade agreements; market access; national treatment; regional comprehensive economic partnership; trade in services